Uma ferramenta de apoio a análise de risco biomecânico de trabalhadores em ambiente informatizado - Falcão, Thayse Justino Montenegro (2018)
The NR-17 establishes parameters that allow the adaptation of the working conditions with psychophysiological characteristics of the workers. The adaptations involve an ergonomic analysis of the workplace, whose main stage is the risk assessment that trigger damaging and irreversible musculoskeletal effects. With the technological advance, we have seen na increasing number of computer-dependent workers, which produce static work overload of the postural muscles that requires recovery mechanisms, is the case of pauses that need to be made for the lubrication of the tendons with synovial fluid and the return of normal blood flow. The literature offers risk assessment devices that are introduced in observational practice or making use of angular analysis software. Such methods become costly, invasive and highly subjective, and provide great variability among examiners. In face of this, the objective was to build an automatic biomechanical risk assessment tool for workers at computerized workstation based on angular limits and risk time present in the literature. To validation a total of 38 administrative workers were included in the study: 26 (68.42%) of the female gender and 12 (31.58%) of the male gender. Evaluated 152 movements and compared with established and used software. The solution developed was able to evaluate neck flexion, trunk inclination, shoulder abduction and flexion abduction and provide a real-time evaluation without the need for markers as the other software do. In addition, the Wilcoxon test showed p-values wich don´t present significant differences in the movements of neck flexion and anterior trunk inclination but did not invalidate similar values between softwares found in abduction of the shoulder. It is concluded that this device is a predominantly preventive evaluation method that is valid due to similar findings between softwares and between the device built with each software. Although some differences have been found in the capture of some movements, it presents a structure that combines practicality, agility and immediate return to the worker, which makes a differential in the specialists practice.